2023
DOI: 10.1088/1475-7516/2023/05/024
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the sources of ultra-high-energy cosmic rays across and above the ankle with the spectrum and composition data measured at the Pierre Auger Observatory

Abstract: In this work we present the interpretation of the energy spectrum and mass composition data as measured by the Pierre Auger Collaboration above 6 × 1017 eV. We use an astrophysical model with two extragalactic source populations to model the hardening of the cosmic-ray flux at around 5 × 1018 eV (the so-called “ankle” feature) as a transition between these two components. We find our data to be well reproduced if sources above the ankle emit a mixed composition with a hard spectrum and a low rigidity cutoff. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 126 publications
3
27
0
Order By: Relevance
“…This feature could indicate a flux of UHE protons with different spectral index to the bulk of the UHECRs, either from a secondary source population or from a single nearby source [15], but it could also originate from a natural mass limit of the mixed UHECR flux. Similar two-component models have been previously studied, either in the context of the transition region between Galactic and extragalactic cosmic rays below 10 18.7 eV [16][17][18][19], or similar to the present paper at the highest energies [20,21].…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…This feature could indicate a flux of UHE protons with different spectral index to the bulk of the UHECRs, either from a secondary source population or from a single nearby source [15], but it could also originate from a natural mass limit of the mixed UHECR flux. Similar two-component models have been previously studied, either in the context of the transition region between Galactic and extragalactic cosmic rays below 10 18.7 eV [16][17][18][19], or similar to the present paper at the highest energies [20,21].…”
Section: Introductionsupporting
confidence: 75%
“…Mild disagreement can be identified for the preferred spectral index of the proton sources, which they predict to be much softer, and the redshift evolution of the mixed-composition sources, which they predict to be substantially stronger. Both of these are likely related the lower limit on the energy range in [19]. They require a larger proton flux below the ankle to explain the entire observed flux while we only use those data points as upper limits.…”
Section: Jcap02(2024)022 6 Discussion and Comparison To Previous Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The observed UHECR spectrum (above 10 18 eV) at Earth mostly follows a E −3 (α ′ ∼ 3) like behaviour and shows breaks at different energies indicating different spectral indices [see 60, for details]. In addition, recent studies by Auger collaboration [see e.g., 61,62] have shown that the mass composition of UHECRs may also influence the spectral index. In fact, these studies suggest that CR spectrum much harder than that predicted by diffusive shock acceleration theory is plausible due to substantial heavy element contribution at highest energies.…”
Section: Gzk Flux: Dependence On Source Propertiesmentioning
confidence: 99%
“…The composition of UHECR: so far, the UHECR primary is considered to be proton only. However, the recent data by Auger [6,[61][62][63][64][65][66] suggests that the UHECR could be composed of heavy elements but the fractional component of these heavy elements is still debatable [36,67,68]. The presence of heavy elements along with protons might lead to lowering of the fluxes of GZK neutrinos and GZK photons [69][70][71].…”
Section: Gzk Flux: Dependence On Source Propertiesmentioning
confidence: 99%